The Influence of Work-Life Balance on Turnover Intention with Job Satisfaction as a Mediating Variable - Ulfatul Munawaroh; I Gusti Ayu Noviekayati; Suhadianto . (CV. ITTC INDONESIA, 2026)
This study aims to examine the effect of work-life balance on turnover intention, with job satisfaction serving as a mediating variable, through a Systematic Literature Review (SLR) approach. Data were synthesized from 13 scientific articles published between 2018 and 2025, sourced from the Google Scholar and ERIC databases. The results indicate that work-life balance exerts a negative influence on turnover intention. Furthermore, job satisfaction was found to mediate the relationship between work-life balance and turnover intention. Consequently, establishing a balance between professional and personal life, alongside enhancing job satisfaction, can effectively reduce employees' intention to leave an organization. These findings offer significant implications for organizational management in designing employee retention strategies by improving work-life balance and job satisfaction.